Application of Triple Exponential Smoothing Method for Predicting the Number of Patients at RSUD dr.Fauziah Bireuen - Maysura; Nurdin; Nunsina (Jurnal Inotera, 2025)
RSUD dr. Fauziah Bireuen is the main referral hospital in Bireuen Regency which has an important role in public health services. Fluctuations in the number of patients per polyclinic are a challenge in managing resources such as medical personnel, medicines, and other supporting facilities. This study aims to apply the triple exponential smoothing method in predicting the number of patients per polyclinic. The results showed that the triple exponential smoothing method has a high level of accuracy with a MAPE value of 1.456% (98.544% accuracy). Predictions using triple exponential smoothing predict 211,460 patients in January 2025, 211,454 in February 2025, and 211,455 for March 2025 to December 2026. Based on these results, triple exponential smoothing is recommended as it provides accurate results and supports the hospital's operational efficiency.